The emergence of a new Turkey : democracy and the AK Parti - Yavuz, M. Hakan (Utah series in Turkish and Islamic studies., 2006)
The start of accession talks between Turkey and the European Union presents an important challenge for Europe and the Muslim world. Although Turkey has often been cited as a model for the accommodation of Islam and secularism, Islam is still a profound factor in Turkish politics. The emergence of a new Turkey explores the conditions under which an Islamic movement or party ceases to be Islamic. It explains the social, economic, and historical origins of the ruling Justice and Development Party, which evolved from Turkey's half-century-old Islamic National Outlook movement, and focuses on the interplay between internal and external forces in the transformation of political Islam into a conservative democratic party. The book also discusses the effect of neoliberal economic policies in Turkey, offering keen insight into one of the most successful transformations of an Islamic movement in the Muslim world.